2021
DOI: 10.3390/jcm10112228
|View full text |Cite
|
Sign up to set email alerts
|

From Desire to Dread—A Neurocircuitry Based Model for Food Avoidance in Anorexia Nervosa

Abstract: Anorexia nervosa is a severe psychiatric illness associated with food avoidance. Animal models from Berridge et al. over the past decade showed that environmental ambience, pleasant or fear inducing, can trigger either appetitive (desire) or avoidance (dread) behaviors in animals via frontal cortex, nucleus accumbens dopamine D1 and D2 receptors, and hypothalamus. Those mechanisms could be relevant for understanding anorexia nervosa. However, models that translate animal research to explain the psychopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 113 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…At last, the understudied domain of biological and neurobiological factors beckons for exploration. The literature presents compelling evidence supporting the relevance of these factors in AN etiology [ 65 67 ]. Additionally, the intricate interaction between biological underpinnings and sociocultural factors, such as the pursuit of the thin ideal, resonates with their involvement in the reward systems of the brain [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…At last, the understudied domain of biological and neurobiological factors beckons for exploration. The literature presents compelling evidence supporting the relevance of these factors in AN etiology [ 65 67 ]. Additionally, the intricate interaction between biological underpinnings and sociocultural factors, such as the pursuit of the thin ideal, resonates with their involvement in the reward systems of the brain [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observations from selfreport studies show that individuals with AN tend to score higher on self-reported punishment and reward sensitivity (Jappe et al, 2011;Jonker et al, 2022). Reports from personality questionnaires show that harm avoidance, a trait predisposing individuals to excessive pessimism and strong inhibitory reactions to punishment or frustration, tends to be elevated in AN (Fassino et al, 2002;Frank et al, 2021). It has also been reported that adults with AN learn less from feedback overall, an effect that persists after weight restoration and correlates with symptom severity (Foerde & Steinglass, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the pathophysiology or biomarkers that characterize brain function in AN and how neurobiology, illness behaviors, and recovery interact (Bulik et al, 2007). Food avoidance and the ability to withstand hunger in AN have led to the hypothesis that brain reward pathways could be altered in the disorder (Faure et al, 2010; Frank, 2021; Frank, Shott, & DeGuzman, 2019). Those circuits have been extensively studied in animal and human brain research (Kelley, 2004; Morales & Berridge, 2020), and behavioral and neuroimaging studies may help elucidate altered brain reward function in AN (Kaye et al, 2013; Monteleone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The absolute value reflects the degree of deviation of the outcome from the expectation and has been conceptualized as a motivational salience signal (D'Ardenne et al, 2013; Fouragnan et al, 2017). The prediction error model is important for AN as it lends itself to a model where conditioned fear of eating and weight gain recruits the sensitized dopamine‐related striatal circuits to override hunger cues and respond to food with dread and avoidance (Castro et al, 2015; Frank, 2021).…”
Section: Introductionmentioning
confidence: 99%